(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
In Venezuela, we have been including government activities based on information technologies (ICTs) allowing the relationship between this and the citizens. Access to information, the application currency and documents of various kinds are being made through the Internet. Certainly it seems that the number of people looking for quick and efficient responses is steadily growing. In this sense, this research has the main objective to analyze whether information technology and especially the Internet, are being used for the delivery by the government, more and better public services to citizens, or whether otherwise have fallen into the pernicious practice of digitization of bureaucracy, which would undermine the true meaning of electronic government (E -Gov). To do this, use the documentary literature, methodology based mainly on the review of legal texts, specialized books and recent studies on e- gob in Venezuela and other countries. One of the main conclusions to those above, is that the possibilities of transformation of Venezuelan public administration through the use of ICT are enormous if really directed towards increasing the efficiency of its management.